Genetics of Severe Cutaneous Adverse Reactions - Yang, Shang-Chen; Chen, Chun-Bing; Lin, Mao-Ying; Zhang, Zhi-Yang; Jia, Xiao-Yan; Huang, Ming; Zou, Ya-Fen; Chung, Wen-Hung (Frontiers in Medicine, 2021)
Severe cutaneous adverse reactions (SCARs) including Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and drug rash with eosinophilia and systemic symptoms (DRESS) are T cells-mediated life-threatening immune reactions, most commonly induced by drug. The last decade has seen significant progress in SCARs research. Recent studies have unveiled the pathogenesis of SCARs involved in susceptible genes, including human leukocyte antigens (HLA) and drugs-T cell receptor (TCR) interaction that may trigger T cell activation with downstream immune signaling of cytokines/chemokines and specific cytotoxic proteins releases. Advances in identification of multiple genetic alleles associated with specific drugs related SCARS in different populations is an important breakthrough in recent years for prevention of SCARs. This article summarized the findings on genetic factors related to SJS/TEN, especially for HLA.